Effects of an Environmental Education Intervention on Environmental Sustainability Among Youth in Malaysia - Rahman, Haliza Abdul; Dahalan, Dzuhailmi; Bakar, Azrin Shah Abu (SCAD Independent, 2023)
Environmental sustainability issues must be disclosed to youths as early as possible to preserve and conserve the environment through formal and informal education. To date, there needs to be more local studies on interventions that encourage positive and behavioral changes that can improve their understanding, knowledge, attitude, and practices toward environmental sustainability. Environmental education intervention is one of the approaches that can be implemented to achieve this goal. This study aimed to evaluate the effects of an environmental education intervention on environmental sustainability among youths. This study was a one-group quasi-experimental study. This study recruited two hundred youths, and the data was collected pre and post-intervention. Respondents in the intervention received an environmental education package (i.e., environmental-based education talk supported with pamphlets and small group discussions). The paired t-test was used to determine the differences between the pre and post-intervention. The study showed a statistically significant difference in pre and post-intervention in understanding, knowledge, attitude, and practices toward environmental sustainability (p < .005). Hence, the environmental education intervention was proven to be effective in increasing environmental sustainability and could serve as an intervention tool among youths in Malaysia to improve environmental protection and conservation.